Linguistic Marginalia: A Special Issue on African Urban Youth Language (AUYL) Practices (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This introduction to the Multilingual Margins special issue on “African Urban and Youth Language (AUYL) Practices” is divided into five parts. The first part presents an overview of urban and youth language practices in Africa, with particular attention paid to the symbolism of youth and urban identity, multilingual composition, and a sample of commons names for AUYL. The second part of the introduction provides an overview of the history of colonial monolingualism and metropolitan infrastructures that created a niche or third space for the multitude of speakers who lacked access to housing, services, and colonial standard languages. The third part of the introduction overviews how the exclusionary policies of colonialism created a marginalization that spawned an informal sector of business, replete with a language of solidarity for the people on the periphery. The fourth part of the introduction discusses how the speakers of AUYL practices are not vicitms or imperial debris, rather they have become agents to localize the global and globalize the local by being fluid enough to renegotiate the colonial with the traditional and engender a reconceptualization of what it means to be globalized and cosmopolitan. Finally, in the fifth part, the introduction presents the eight articles that constitute the special issue.